Review of Chinese species of genus Paramritodus Xue & Zhang (Hemiptera: Cicadellidae) with description of a new species - Yu, Tingting; Zhu, Qiuyi; Li, Guoqing; Zhang, Bin (Zootaxa, 2024)
The Chinese leafhopper species of the genus Paramritodus Xue & Zhang are reviewed. One new species, Paramritodus concavicaudus Zhang sp. nov., is described and illustrated from southwest China. Additionally, Paramritodus flavocapitatus (Cai & He, 2001) is proposed as a junior synonym of Paramritodus pistacious (Huang & Maldonado Capriles, 1992). A key to the species of the genus is also provided.